The paradox of legality-vis-à-vis morality in contemporary Islamic law: an analysis of the Sunni legal debate on sex selection - Haneef, Sayed Sikandar Shah (LexisNexis, 2017)
This paper discusses the issue of dislocation of morality from legality in the predominant jursitci legal stand on sex selection among the contemporary Sunni Muslim legists. Similar to Western divide between positivist school and natural law advocates on the legality of some biomedical issues, such as stem cell research, it is puzzling that Muslim jurists of our age also have contested positions on a host of biomedical issues, such as fetal sex selection. Vast majority legard it as legitimate with minimum restriction while dissenting voices see it as immoral and hence legally unlawful. This paper, however, argues that had supporters reflected more on numerous ethical questions which surround the procedure and consequences of medical sex selection , they would have come to a more morally sensitive legal verdict.